An exploratory study on the study abroad decision and international students’ perception on the risk associated. - Cao, Minh Trang (2012)
In recent years, the demand for international education has dramatically increased as people realise the importance of gaining a set of global skills and international knowledge. The globalisation pressure has led to an internationalised and highly competitive environment within the education sector. The enormous demand raises the need for a better understanding of the prospective customers’ behaviour towards international education as a source of competitive advantage. There has been an increasing body of literature studying international students’ motives behind the decision to study abroad. However, little has been done to examine the risky aspect of such decision despite the various inherent risks associated (Luethege, 2004).